Music Streaming's Impact on Cultural Diversity : Spotify and Recommendation Algorithms as Gatekeepers - Leino, Jenni (My University, 2023)
The rapid growth of music streaming business has brought significant changes to the music industry, creating new opportunities for artists, labels, and consumers alike. Streaming services, like Spotify, use algorithmic recommendation systems to help users find the content relevant to them from the seemingly endless trove of music. As modern gatekeepers, these services – and the algorithms they use – yield significant power over culture, affecting the rights of both artists and listeners. This thesis examines the music business in the digitalized era, the algorithmic recommendation of music, and its impact on cultural diversity, the right to express and access culture. Additionally, I will examine what kinds of methods the international society, UN at its helm, has proposed to protect cultural rights and diversity.

Musiikin suoratoistopalveluiden nopea kasvu on muuttanut musiikkialaa merkittävästi, luoden uusia mahdollisuuksia niin artisteille, levy-yhtiöille kuin kuluttajillekin. Suoratoistoalustat, kuten Spotify, käyttävät suosittelualgoritmeja ja koneoppimista helpottaakseen käyttäjälle relevantin sisällön löytämistä musiikin loputtomasta tulvasta. Moderneina portinvartijoina suoratoistopalveluilla – ja näin myös niiden käyttämillä suosittelualgoritmeilla – on paljon kulttuurista valtaa. Opinnäytetyössäni tutkin, minkälaisia vaikutuksia suoratoistopalveluilla ja suosittelualgoritmeilla, voi olla ihmisoikeuksiin; kulttuuriseen monimuotoisuuteen, ilmaisunvapauteen ja pääsyyn kulttuurin äärelle. Lisäksi tutkin, minkälaisia toimia kansainvälinen yhteisö YK:n johdolla on ehdottanut kulttuuristen oikeuksien turvaamiseksi.
Keywords: Algorithmic recommendation, cultural diversity, digitalisation, gatekeeping, human rights, music streaming, right to culture, digitalisaatio, ihmisoikeudet, kulttuuriset oikeudet, musiikin suoratoisto, portinvartijat, suosittelualgoritmi